2021
DOI: 10.1038/s41467-021-26285-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple evolutionary origins and losses of tooth complexity in squamates

Abstract: Teeth act as tools for acquiring and processing food, thus holding a prominent role in vertebrate evolution. In mammals, dental-dietary adaptations rely on tooth complexity variations controlled by cusp number and pattern. Complexity increase through cusp addition has dominated the diversification of mammals. However, studies of Mammalia alone cannot reveal patterns of tooth complexity conserved throughout vertebrate evolution. Here, we use morphometric and phylogenetic comparative methods across fossil and ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 131 publications
2
17
0
Order By: Relevance
“…Among other studies that have emphasized the importance of the KTR in squamate evolution is Lafuma et al, 2021 . In a study of origins and losses of tooth complexity across the clade, they found that tooth complexity first increased in the Late Jurassic, although it is regarded as marginal until the KTR.…”
Section: Discussionmentioning
confidence: 99%
“…Among other studies that have emphasized the importance of the KTR in squamate evolution is Lafuma et al, 2021 . In a study of origins and losses of tooth complexity across the clade, they found that tooth complexity first increased in the Late Jurassic, although it is regarded as marginal until the KTR.…”
Section: Discussionmentioning
confidence: 99%
“…Lepidosaurian reptiles, including Squamata (lizard and snakes) and Rhynchocephalia (tuatara and extinct relatives), are extremely diverse and represent ideal model systems to assess major aspects of tooth diversity found in nonmammalian lineages. In this group, species represent a multitude of ecologies and show a large array of dental phenotypes, ranging from simple conical to complex multicuspid teeth, directly reflecting dietary specialization ( 19 ). Some lepidosaurs also bear atypical heterodont dentitions, signifying that they bear teeth with different shapes or implantation modes in different parts of the skull and/or jaw, while others are homodont, having only one tooth type ( 15 , 18 , 20 , 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, EDAR localizes to the inner enamel epithelium (IEE), although its distribution is more widespread toward the cervical loops than in mouse. Since EDA is a key regulator of tooth shape evolution across vertebrates ( 3 , 4 ), this differential expression pattern could potentially contribute to some differences between mouse and lizard dental morphology ( 19 , 38 ). Additional EDA expression sites not previously described include the mesenchymal condensation and IEE at cap and bell stages, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Meiri & Levin 2 open their comment with three ‘key mammalian characteristics’ they claim that Morganucodon and Kuehneotherium possessed. None of these characters is a key characteristic associated with the origin of crown group Mammalia: a) multi-cusped teeth considerably predate these Late Triassic/Early Jurassic mammaliaforms 20 and are widely found in reptiles 22 , whereas diphyodonty and notably complex occlusion first appear in such mammaliaforms 1 , 23 ; b) as noted above, ossified respiratory turbinates, as found in extant mammals, are not present in Morganucodon nor Kuehneotherium (but do appear outside crown group Mammalia 19 , 20 ); and c) Harderian glands are universal throughout tetrapods, while their association with grooming and pelage maintenance is unknown beyond rodents 24 and cannot be used to infer the presence of fur in the mammaliaforms Morganucodon and Kuehneotherium .…”
Section: Discussionmentioning
confidence: 99%